Możliwości wykorzystania modelu biznesowego Dyrygenta na przykładzie firmy z sektora zarządzania nieruchomościami - Drzewiecki, Jakub (The opportunities of application of conductor business model in a real estate management company, 2005)
The goal of the article is to show the opportunities of application of business models in real estate management. The article is based upon the classification of business models proposed by Obłoj, with focus on the Conductor model. The article also describes an example of a company operating in the real estate management sector and using the Conductor model. The paper contains specific features of this business model according to changes occurring in the described company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 235-245